Angiographic Findings and Revascularization Success in Patients With Acute Myocardial Infarction and Previous Coronary Bypass Grafting - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Röther, Jens; Nef, Holger; Hamm, Christian; Schlundt, Christian (American Journal of Cardiology, 2016)
Current guidelines recommend invasive coronary angiography and interventional revascularization in ST-elevation and Non-ST-elevation myocardial infarction (STEMI and NSTEMI). The aim of this study was to analyze culprit lesions and percutaneous coronary intervention (PCI) success in patients with previous coronary artery bypass grafting (CABG). We analyzed the data of 121 consecutive patients in whom coronary angiography was performed in the setting of STEMI or NSTEMI and who had previous CABG. Coronary angiograms were reviewed, and clinical data were evaluated. The culprit vessel was identified by means of electrocardiographic findings, echocardiography, and coronary angiography. A bypass graft was the culprit vessel in 86% of patients with STEMI and 68% of patients with NSTEMI. Venous grafts were culprit vessels significantly more frequently than arterial grafts (81 of 260 venous grafts vs 4 of 65 arterial grafts, p <0.001). Attempted acute PCI was successful in 97% of native arteries (31 of 32 patients) but only in 81% of bypass grafts (68 of 84 patients, p = 0.031). Overall in-hospital mortality was 13% (STEMI: 25%, NSTEMI: 10%, p <0.001) and was significantly higher after failed acute PCI (6 of 11 patients; 55%) compared with successful acute PCI (7 of 110 patients; 6%; p = 0.006). In conclusion, the culprit lesion in patients with previous CABG who present with STEMI or NSTEMI is more often located in bypass grafts than in native arteries. Successful PCI is more likely in native arteries compared with bypass grafts.
EVALuna2:33683

Applicability and procedural success rate of bioresorbable-vascular scaffolds for percutaneous coronary intervention in an all-comer cohort of 383 consecutive patients - Schlundt, Christian; Achenbach, Stephan; Felten, Fabiola; Röther, Jens; Nef, Holger; Ludwig, Josef; Tröbs, Monique; Marwan, Mohamed (Acta Cardiologica, 2017)
Objectives The purpose of this study was to determine applicability and procedural success of bioresorbable vascular scaffolds (BVS) for percutaneous coronary intervention (PCI) in an all-comer cohort. Background BVS use in bifurcations and severely calcified lesions is not recommended, and a relatively large crossing profile may cause limitations. It is has never been studied how widely BVS can be applied in all-comer cohorts. Methods In 383 consecutive patients (acute coronary syndrome: 124, stable coronary disease 259), a BVS (Absorb) was used as first-line device unless any of the following contraindications were present: bifurcation with side branch >2.0 mm, reference diameter <2.5 mm or >4.0 mm, required device length <12 mm, in-stent stenosis, or contraindications to 6 months of DAPT. Patients and lesions were evaluated regarding suitability for BVS treatment, procedural success (successful BVS placement and residual stenosis <30%), and outcome. Results Of 588 lesions, 303 (52%) were unsuitable for BVS placement due to presence of a bifurcation (30% of unsuitable lesions), reference -diameter >4.0 mm (13%) or <2.5 mm (12%), contraindication to 6 months DAPT (13%), in-stent stenosis (14%), and desired device length <12 mm (4%). If BVS use was attempted, procedural success with a scaffold was 95% (271/285). Crossing failure occurred in 14 cases (5%), affected lesions were significantly more calcified. After a mean follow-up period of 259 days, definite/probable scaffold thrombosis occurred in 1.1% of patients. Conclusions Approximately one-half of lesions in an all-comer population can successfully be treated with BVS. Crossing failure is rare.
EVALuna2:33655

Bioresorbable vascular scaffold thrombosis in a consecutive cohort of 550 patients - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Klinghammer, Lutz; Schlundt, Christian (Catheterization and Cardiovascular Interventions, 2016)
OBJECTIVE: To determine the rate of bioresorbable vascular scaffold (BVS) thrombosis in a large, real-world population. BACKGROUND: There is some concern about device thrombosis after percutaneous coronary intervention (PCI) using BVS. No data have been published for PCI using both BVS and metal stents. METHODS: A cohort of 550 consecutive patients who underwent PCI for stable chest pain or acute coronary syndromes with implantation of at least one BVS (Absorb, Abbott Vascular) was systematically followed up by telephone interview and review of medical charts. Data on device thrombosis were retrospectively analyzed in relationship to clinical and angiographic characteristics. RESULTS: Follow-up was achieved in 533 patients (97%, median follow-up 233 days). A total of 964 BVS were implanted in 645 vessels. In addition, 234 metal stents were implanted in 149 patients, including "hybrid intervention" with the combined use of BVS and stents in the same artery in 122 patients. Documented were 15 definite, 1 probable, and 8 possible cases of device thrombosis (rate of definite/probable device thrombosis: 3.0%). Of these, 6 definite and 6 possible thromboses could be unambiguously attributed to BVS (1.1%), whereas a total of 11 definite, 1 probable, and 8 possible thromboses were potentially attributable to BVS (2.3%). Definite device thrombosis occurred in 7/122 patients with "hybrid intervention" (5.7%). CONCLUSIONS: In a large real-world cohort treated with BVS, the rate of scaffold thrombosis was higher than published for randomized trials. A high rate of thrombosis was observed after combined implantation of BVS and stents within one vessel. © 2016 Wiley Periodicals, Inc.
EVALuna2:33663

Changes of tricuspid valve geometry after interventional implantation of an anuloplasty band - Landendinger, M.; Smolka, S.; Haug, J.; Tröbs, Monique; Ammon, Fabian; Achenbach, Stephan; Arnold, Martin; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Comparison of adenosine-independent pressure indices to fractional flow reserve in stent-jailed bifurcation side branches - Altstidl, Johannes Michael; Achenbach, Stephan; Marwan, Mohamed; Tröbs, Monique; Schacher, Nora; Ferstl, Paul; Gerlach, Andreas; Schlundt, Christian; Gaede, Luise (Catheterization and Cardiovascular Interventions, 2022)
Objectives and Background: This study aims to evaluate whether the high correlation and classification agreement of the instantaneous wave-free ratio (iFR) and the resting distal coronary to aortic pressure ratio (Pd/Pa) with the fractional flow reserve (FFR) can be confirmed in stent-jailed side branches (J-SB). Methods: Consecutive patients (n = 49) undergoing provisional stenting were prospectively enrolled and a physiological assessment of the J-SB (n = 51) was performed. FFR, iFR, and Pd/Pa were measured and the hemodynamic relevance was determined using cutoff values of ≤0.80, ≤0.89, and ≤0.92, respectively. Results: Both iFR (r = 0.75) and Pd/Pa (r = 0.77) correlated closely with FFR. Classification agreement with FFR was 78% for iFR (81% sensitivity, 77% specificity) and 75% for Pd/Pa (63% sensitivity and 80% specificity). However, angiographic diameter stenosis and pressure indices correlated poorly. For a threshold of ≥70% stenosis, agreement concerning hemodynamic relevance was found in 59% for FFR, 69% for iFR, and 61% for Pd/Pa. Conclusion: As reported for other lesion types, FFR and the adenosine-independent pressure indices iFR and Pd/Pa show close correlation and a high classification agreement of approximately 75%–80% in J-SB. Therefore, iFR can be regarded as a recommendable alternative to FFR for the guidance of provisional stenting in bifurcation lesions.
CRIS-Team Scopus Importer:2022-07-01
Keywords: catheterization diagnostic; coronary artery disease; fractional flow reserve

Comparison of fractional flow reserve and instantaneous wave-free ratio for the hemodynamic assessment of jailed side branches in bifurcation stenting - Altstidl, J. M.; Tröbs, Monique; Achenbach, Stephan; Gaede, L.; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Comparison of Fractional Flow Reserve Based on Computational Fluid Dynamics Modeling Using Coronary Angiographic Vessel Morphology Versus Invasively Measured Fractional Flow Reserve - Tröbs, Monique; Achenbach, Stephan; Röther, Jens; Redel, Thomas; Scheuering, Michael; Winneberger, David; Klingenbeck, Klaus; Itu, Lucian; Passerini, Tiziano; Kamen, Ali; Sharma, Puneet; Comaniciu, Dorin; et al. (American Journal of Cardiology, 2016)
Invasive fractional flow reserve (FFRinvasive), although gold standard to identify hemodynamically relevant coronary stenoses, is time consuming and potentially associated with complications. We developed and evaluated a new approach to determine lesion-specific FFR on the basis of coronary anatomy as visualized by invasive coronary angiography (FFRangio): 100 coronary lesions (50% to 90% diameter stenosis) in 73 patients (48 men, 25 women; mean age 67 ± 9 years) were studied. On the basis of coronary angiograms acquired at rest from 2 views at angulations at least 30° apart, a PC-based computational fluid dynamics modeling software used personalized boundary conditions determined from 3-dimensional reconstructed angiography, heart rate, and blood pressure to derive FFRangio. The results were compared with FFRinvasive. Interobserver variability was determined in a subset of 25 narrowings. Twenty-nine of 100 coronary lesions were hemodynamically significant (FFRinvasive <=0.80). FFRangio identified these with an accuracy of 90%, sensitivity of 79%, specificity of 94%, positive predictive value of 85%, and negative predictive value of 92%. The area under the receiver operating characteristic curve was 0.93. Correlation between FFRinvasive (mean: 0.84 ± 0.11) and FFRangio (mean: 0.85 ± 0.12) was r = 0.85. Interobserver variability of FFRangio was low, with a correlation of r = 0.88. In conclusion, estimation of coronary FFR with PC-based computational fluid dynamics modeling on the basis of lesion morphology as determined by invasive angiography is possible with high diagnostic accuracy compared to invasive measurements.
EVALuna2:12050

Comparison of invasively measured FFR with FFR derived from coronary CT angiography for detection of lesion-specific ischemia: Results from a PC-based prototype algorithm - Röther, Jens; Moshage, Maximilian; Dey, Damini; Schwemmer, Chris; Tröbs, Monique; Blachutzik, Florian; Achenbach, Stephan; Schlundt, Christian; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2018)
BACKGROUND: We evaluated the diagnostic accuracy of a novel prototype for on-site determination of CT-based FFR (cFFR) on a standard personal computer (PC) compared to invasively measured FFR in patients with suspected coronary artery disease. METHODS: A total of 91 vessels in 71 patients (mean age 65 ± 9 years) in whom coronary CT angiography had been performed due to suspicion of coronary artery disease, and who subsequently underwent invasive coronary angiography with FFR measurement were analyzed. For both cFFR and FFR, a threshold of ≤0.80 was used to indicate a hemodynamically relevant stenosis. The mean time needed to calculate cFFR was 12.4 ± 3.4 min. A very close correlation between cFFR and FFR could be shown (r = 0.85; p < 0.0001) with Bland-Altman analysis showing moderate agreement between FFR and cFFR with mild systematic overestimation of FFR values in CT (mean difference 0.0049, 95% limits of agreement ±2SD -0.007 to 0.008). Compared to FFR, the sensitivity of cFFR to detect hemodynamically significant lesions was 91% (19/21, 95% CI: 70%-99%), specificity was 96% (67/70, 95% CI: 88%-99%), positive predictive value 86% (95% CI: 65%-97%) and negative predictive value was 97% (95% CI: 90%-100%) with an accuracy of 93%. CONCLUSION: cFFR obtained using an on-site algorithm implemented on a standard PC shows high diagnostic accuracy to detect lesions causing ischemia as compared to FFR. Importantly, the time needed for analysis is short which may be useful for improving clinical workflow.
EVALuna2:36006

Comparison of standard- and high-dose intracoronary adenosine for the measurement of coronary fractional flow reserve (FFR) - Röther, Jens; Achenbach, Stephan; Tröbs, Monique; Blachutzik, Florian; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Clinical Research in Cardiology, 2016)
BACKGROUND: Measurement of fractional flow reserve (FFR) by intravenous infusion or intracoronary injection of adenosine is the reference method to determine the hemodynamic relevance of coronary artery stenoses. The goal of this prospective study was to compare standard (40 µg adenosine for the right and 80 µg for the left coronary artery) to high doses of intracoronary adenosine for FFR measurement. METHODS AND RESULTS: In 130 intermediate coronary artery stenoses, two sequential FFR measurements were performed with standard-dose intracoronary application of adenosine (40 µg for the right and 80 μg for the left coronary artery), followed by one FFR measurement with a bolus of 200 μg for the right and 400 μg for the left coronary artery. There was strong correlation (r = 0.97, p < 0.001) between FFR values determined with standard-dose adenosine (0.86 ± 0.08) versus high-dose adenosine (0.85 ± 0.08). High-dose adenosine did not yield FFR values ≤0.80 or ≤0.75 significantly more frequently than standard-dose adenosine. Patients reported more discomfort after high-dose adenosine application compared to standard-dose adenosine (p < 0.001). CONCLUSIONS: For FFR measurements with intracoronary adenosine injection, results achieved with doses of 40 µg adenosine for the right and 80 µg for the left coronary artery display no clinically relevant difference to doses of 200 and 400 µg, respectively.
EVALuna2:33662

Computed Tomography Angiography Reply - Tröbs, Monique (Deutsches Ärzteblatt international, 2019)
CRIS-Team WoS Importer:2019-10-08

Computer-aided evaluation of low-dose and low-contrast agent third-generation dual-source CT angiography prior to transcatheter aortic valve implantation (TAVI) - Dankerl, Peter; Hammon, Matthias; Seuß, Hannes; Tröbs, Monique; Schuhbaeck, Annika; Hell, Michaela M.; Achenbach, Stephan; Uder, Michael; Marwan, Mohamed; Cavallaro, Alexander Josef (International Journal of Computer Assisted Radiology and Surgery, 2016)
To evaluate the performance of computer-aided evaluation software for a comprehensive workup of patients prior to transcatheter aortic valve implantation (TAVI) using low-contrast agent and low radiation dose third-generation dual-source CT angiography.We evaluated 30 consecutive patients scheduled for TAVI. All patients underwent ECG-triggered high-pitch dual-source CT angiography of the aortic root and aorta with a standardized contrast agent volume (30 ml Imeron350, flow rate 4 ml/s) and low-dose (100 kv/350 mAs) protocol. An expert (10 years of experience) manually evaluated aortic root and iliac access dimensions (distance between coronary ostia and aortic annulus, minimal/maximal diameters and area-derived diameter of the aortic annulus) and best CT-predicted fluoroscopic projection angle as the reference standard. Utilizing computer-aided software (syngo.via), the same pre-TAVI workup was performed and compared to the reference standard.Mean CTDI[Formula: see text] was 3.46 mGy and mean DLP 217.6 ± 12.1 mGy cm, corresponding to a mean effective dose of 3.7 ± 0.2 mSv. Computer-aided evaluation was successful in all but one patient. Compared to the reference standard, Bland-Altman analysis indicated very good agreement for the distances between aortic annulus and coronary ostia (RCA: mean difference 0.8 mm; 95 % CI 0.4-1.2 mm; LM: mean difference 0.9 mm; 95 % CI 0.5-1.3 mm); however, we demonstrated a systematic overestimation of annulus- derived diameter using the software (mean difference 44.4 mm[Formula: see text]; 95 % CI 30.4-58.3 mm[Formula: see text]). Based on respective annulus dimensions, the recommended prosthesis size (Edwards SAPIEN 3) matched in 26 out of the 29 patients (90 %). CT-derived fluoroscopic projection angles showed an excellent agreement for both methods. Out of 58 iliac arteries, 15 (25 %) arteries could not be segmented by the software. Preprocessing time of the software was 71 ± 11 s (range 51-96 s), and reading time with the software was 118 ± 31 s (range 68-201 s).In the workup of pre-TAVI CT angiography, computer-aided evaluation of low-contrast, low-dose examinations is feasible with good agreement and quick reading time. However, a systematic overestimation of the aortic annulus area is observed.
EVALuna2:14602

Coronary Angiography With Pressure Wire and Fractional Flow Reserve State of the Art in the Diagnosis of Coronary Stenosis - Gaede, Luise; Moellmann, Helge; Rudolph, Tanja; Rieber, Johannes; Boenner, Florian; Tröbs, Monique (Deutsches Ärzteblatt international, 2019)
Background: Approximately 800 000 coronary angiography procedures are per formed in Germany each year, mainly in order to identify coronary artery stenoses. As a rule, revascularization is indicated only when coronary artery stenoses cause relevant ischemia, but this cannot be determined unequivocally by angiography alone. Pressure wire measurement and the measurement of fractional flow reserve (FFR) enable direct evaluation of the hemodynamic relevance of coronary artery stenoses during diagnostic coronary angiography.
CRIS-Team WoS Importer:2019-05-21

Coronary Computed Tomographic Angiography Can Predict Chronic Total Occlusion Recanalization Success: Where Do We Go From Here? - Achenbach, Stephan; Tröbs, Monique (Journal of the American College of Cardiology : Cardiovascular imaging, 2018)
EVALuna2:33583

Coronary Stent Strut Fractures: Classification, Prevalence and Clinical Associations - Schochlow, Katharina; Weissner, Melissa; Blachutzik, Florian; Boeder, Niklas F.; Tröbs, Monique; Lorenz, Liv; Dijkstra, Jouke; Munzel, Thomas; Achenbach, Stephan; Nef, Holger; Gori, Tommaso (Journal of Clinical Medicine, 2021)
Introduction. The frequency, characteristics and clinical implications of Strut fractures (SFs) remain incompletely understood. Methods and results. A total of 185 (160 patients) newer-generation drug-eluting stents (DES) were imaged. SFs were found in 21 DES (11.4%) and were classified in four patterns: one single stacked strut (41%); two or more stacked struts (23%); deformation without gap (27%); transection (9%). In multivariable analysis, calcific and bifurcation lesions were associated with SF in DES (OR: 3.5 [1.1-11] and 4.0 [2.2-7.2], p < 0.05). Device eccentricity and asymmetry as well as optical coherence tomography (OCT) features of impaired strut healing were also associated with SF. The prevalence of fractures was similar in a set of 289 bioresorbable scaffolds (BRS). In a separate series of 20 device thromboses and 36 device restenoses, the prevalence of SF was higher (61.2% of DES and 66.7% of BRS, p < 0.001 for both), with a higher frequency of complex SF patterns (p < 0.0001). In logistic regression analysis, fractures were a correlate of device complications (p < 0.0001, OR = 24.9 [5.6-111] for DES and OR = 6.0 [1.8-20] for BRS). Discussion. The prevalence of OCT-diagnosed SF was unexpectedly high in the setting of elective controls and it increased by about three-fold in the setting of device failure. Fractures were associated with increased lesion complexity and device asymmetry/eccentricity and were more frequent in the setting of device failure such as restenosis and thrombosis.
CRIS-Team WoS Importer:2021-05-07

Double kissing - crush technique to treat coronary bifurcation lesions: analysis of success rate, procedural times and device usage - Schacher, Nora; Ferstl, Paul; Weidinger, Franz; Achenbach, Stephan; Tröbs, Monique; Marwan, Mohamed; Gaede, Luise (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Early single center experience with a novel transcatheter anuloplasty system for the treatment of functional tricuspid regurgitation - Landendinger, M.; Smolka, S.; Tröbs, Monique; Anneken, Lars; Gaede, L.; Achenbach, Stephan; Arnold, Martin; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2020)
CRIS-Team WoS Importer:2021-02-12

Effect of non-compliant balloon postdilatation on magnesium-based bioresorbable vascular scaffolds - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Weissner, Melissa; Nef, Holger; Schlundt, Christian; Marwan, Mohamed (Catheterization and Cardiovascular Interventions, 2019)
Background: Optimal implantation results of bioresorbable scaffolds (BRS) are typically assumed to require postdilatation with non-compliant (NC) balloons to achieve full scaffold apposition and minimize event rates. We systematically evaluated the mechanical effect of NC balloon postdilatation on magnesium-based BRS (Magmaris (R), Biotronik AG, Bulach, Switzerland) in vivo.
CRIS-Team WoS Importer:2019-03-08

Everolimus eluting bioresorbable vascular scaffolds in patients with acute coronary syndromes: Two-year results from the German-Austrian ABSORB registry - Tröbs, Monique; Achenbach, Stephan; Nef, Holger M.; Gori, Tomasso; Naber, Christoph; Neumann, Till; Richardt, Gert; Schmermund, Axel; Woehrle, Jochen; Zahn, Ralf; Hamm, Christian W. (Catheterization and Cardiovascular Interventions, 2021)
Objectives To identify potential differences in 2-year outcome between patients who underwent coronary revascularization using bioresorbable vascular scafffolds (BVS) in stable coronary artery disease (CAD) and acute coronary syndromes (ACS).
CRIS-Team WoS Importer:2021-07-02

Impact of COVID-19 lockdown on the procedural and intra-hospital outcome of STEMI patients - Gaede, Luise; Rittger, H.; Gerrens, H.; Achajew, A.; Schacher, Nora; Ferstl, Paul; Tröbs, Monique; Arnold, Martin; Marwan, Mohamed; Achenbach, Stephan (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Incidental Finding of Strut Malapposition Is a Predictor of Late and Very Late Thrombosis in Coronary Bioresorbable Scaffolds - Boeder, Niklas F.; Weissner, Melissa; Blachutzik, Florian; Ullrich, Helen; Anadol, Remzi; Tröbs, Monique; Muenzel, Thomas; Hamm, Christian W.; Dijkstra, Jouke; Achenbach, Stephan; Nef, Holger M.; Gori, Tommaso (Journal of Clinical Medicine, 2019)
Malapposition is a common finding in stent and scaffold thrombosis (ScT). Evidence from studies with prospective follow-up, however, is scarce. We hypothesized that incidental observations of strut malapposition might be predictive of late ScT during subsequent follow-up. One hundred ninety-seven patients were enrolled in a multicentre registry with prospective follow-up. Optical coherence tomography (OCT), performed in an elective setting, was available in all at 353 (0-376) days after bioresorbable scaffold (BRS) implantation. Forty-four patients showed evidence of malapposition that was deemed not worthy of intervention. Malapposition was not associated with any clinical or procedural parameter except for a higher implantation pressure (p = 0.0008). OCT revealed that malapposition was associated with larger vessel size, less eccentricity (all p < 0.01), and a tendency for more uncovered struts (p = 0.06). Late or very late ScT was recorded in seven of these patients 293 (38-579) days after OCT. OCT-diagnosed malapposition was a predictor of late and very late scaffold thrombosis (p < 0.001) that was independent of the timing of diagnosis. We provide evidence that an incidental finding of malappositionregardless of the timing of diagnosis of the malappositionduring an elective exam is a predictor of late and very late ScT. Our data provide a rationale to consider prolonged dual antiplatelet therapy if strut malapposition is observed.
CRIS-Team WoS Importer:2019-06-25

Increased risk for vascular complications due to GP IIb/IIIa-antagonists in patients with cardiogenic shock supported by intraaortic balloon pump (IABP) - Röther, Jens; Tröbs, Monique; Schuhbäck, Annika; Ludwig, Josef; Achenbach, Stephan; Schlundt, Christian (Clinical Trials and Regulatory Science in Cardiology, 2015)
Background IABP is routinely used to support coronary blood flow and systemic circulation in patients with cardiogenic shock. Our aim was to explore the incidence of vascular complications associated with the use of IABP in this scenario and their influence on mortality. Methods Therefor we analysed 204 consecutive patients between 2002 and 2013 treated with IAPB in cardiogenic shock for vascular complications and mortality within 30 days after implantation of IAPB. Primary endpoints were severe bleeding (TIMI-definition: intracranial bleeding, loss of haemoglobin (Hb) > 5 g/dl or haematocrit (PCV) > 15%), vascular complications with therapeutic consequence (venous thrombosis, arterial embolism) and stroke. Results 80 (39%) patients died within 30 days after implantation of IABP. In 42 (21%) patients, vascular complications occurred: severe bleeding was present in 26 patients (62% of all complications), 13 (31%) patients suffered from venous thrombosis or arterial embolism and 3 (7%) patients from stroke. 25% of the patients who died had a vascular complication. The rate in patients who overcame cardiogenic shock was 17.7% (p = 0.22). Multivariate analyses showed treatment with Glycoprotein (GP) IIb/IIIa- inhibitors to be an independent risk factor for the occurrence of vascular complications (p = 0.04). Conclusion Vascular events with the use of IABP are common but in our study, not significantly associated with a higher mortality. Treatment with GP IIb/IIIa-antagonists is associated with a higher risk of vascular events.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cardiogenic shock; GP IIb/IIIa-antagonists; IABP; Vascular complications

Indications, procedural parameters, complications and consequences of fractional flow reserve measurements in a multicenter cohort - Tröbs, Monique; Gaede, L.; Feyrer, J.; Nazli, B.; Moellmann, H.; Giesler, T.; Rittger, H.; Pauschinger, M.; Rudolph, T.; Moshage, W.; Brueck, M.; Achenbach, Stephan; et al. (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Influence of sex on results and consequences of coronary fractional flow reserve in clinical practice: results of a prospective large-scale multicenter registry - Tröbs, Monique; Marwan, Mohamed; Gaede, Luise; Moellmann, H.; Giesler, T.; Rittger, H.; Rudolph, T.; Pauschinger, M.; Moshage, W.; Brueck, M.; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Left ventricular contraction patterns in Takotsubo Syndrome and their correlation with long-term clinical outcome - Gaede, Luise; Herchenbach, Amanda; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed (IJC Heart & Vasculature, 2021)
Background: Takotsubo Syndrome (TTS) is diagnosed in 1–2% of all patients presenting with acute coronary syndrome. Next to the typical apical manifestation, other locations of left ventricular contraction abnormality are possible, but their relationship to patient characteristics, clinical correlates as well as long-term outcome are poorly understood. Methods & results: We retrospectively analyzed 126 patients presenting TTS. Cases were categorized according to left ventricular contraction abnormality patterns: typical apical pattern (71%, n = 89) vs. atypical patterns (29%, n = 37). Cases with typical TTS showed significantly higher levels of troponin I (3.12 ng/ml vs. 1.32 ng/ml, p = 0.013) and creatin kinase (CK) on admission (461 (±1207)U/l vs. 173 (±177) U/l, p = 0.03) as well as peak CK (973 (±2860)U/l vs. 301 (±328) U/l, p = 0.03) and more often ischemia related ECG changes (p = 0.02). Follow-up data was available for 85% of the patients. Median FU time was 4.4 years (IQR 1.4–7.7 years). All-cause mortality during follow-up was 39%, with no significant difference between patients with typical or atypical TTS (43% vs. 29%, p = 0.17). In multivariate logistic regression analysis, only anemia was predictive for long-term mortality (OR 3.93, 95%CI 1.02–2.08, p = 0.015). The majority of surviving patients (69%) reported good quality of life, even though only 56% reported being symptom-free. Conclusion: Patients with TTS have poor long-term prognosis with an overall mortality of 39.1% within 4 years and nearly half of all patients report persisting symptoms. Even though the apical contraction pattern is associated with higher elevation of serum markers for myocardial damage, it was not associated with higher long-term mortality.
CRIS-Team Scopus Importer:2021-01-15
Keywords: Broken heart syndrome; Contraction pattern; Stress cardiomyopathy; Takotsubo cardiomyopathy; Takotsubo Syndrome

Major coronary evaginations following implantation of bioresorbable vascular scaffolds: clinical and OCT characteristics - Blachutzik, F.; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, R.; Weissner, M.; Schlundt, Christian; Marwan, Mohamed (2017)
EVALuna2:36025

Major coronary evaginations following implantation of bioresorbable vascular scaffolds - Clinical and OCT characteristics - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Nef, Holger; Weissner, Melissa; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2019)
Background: Coronary evaginations can occur after implantation of bioresorbable vascular scaffolds (BRS) and may be associated with scaffold thrombosis. Aim of this study was to clarify the clinical manifestation, extent and time course of coronary artery remodeling in vessel segments that develop angiographically detectable evaginations following BRS implantation through optical coherence tomography (OCT) analysis.
CRIS-Team WoS Importer:2019-06-18

New ESC heart failure guideline - significance for general practitioners. - Tröbs, Monique; Achenbach, Stephan (MMW Fortschritte der Medizin, 2017)
EVALuna2:36043

OCT-assessment of scaffold resorption: Analysis of strut intensity by a new resorption index for poly-l-lactic acid bioresorbable vascular scaffolds - Blachutzik, Florian; Achenbach, Stephan; Tröbs, Monique; Boeder, Niklas; Doerr, Oliver; Weissner, Melissa; Bauer, Timm; Nef, Holger; Hamm, Christian; Schlundt, Christian; Marwan, Mohamed (Catheterization and Cardiovascular Interventions, 2019)
Background: The aim of this study was to analyze individual differences in resorption of bioresorbable vascular scaffolds (BRS) through optical coherence tomography (OCT) analysis and to identify factors potentially influencing the resorption process. Methods: Between April 2016 and July 2017 clinically driven invasive coronary angiography and OCT examinations were performed in 36 patients who had previously been treated with a total of 48 BRS (ABSORB BVS, Abbott Vascular, Santa Clara, CA). For each scaffold, a new BRS-RESORB-INDEX (BRI) was calculated. Results: The mean time interval since implantation was 789 ± 321 days. In OCT, BRS struts remained detectable in all 48 BRS. Normalized light intensity as a marker for the resorption of BRS struts increased with time in a linear fashion (Spearman Rho: p <.001, correlation coefficient =.90; R 2 [linear] =.91). Multivariable analysis identified diabetes (BRI of patients with diabetes vs. patients without diabetes: 0.34 ± 0.13 vs. 0.58 ± 0.22; p =.002) and presence of Peri-strut low intensity areas (PSLIA, BRI of 10 patients with PSLIA vs. 26 patients without PSLIA: 0.44 ± 0.21 vs. 0.61 ± 18; p =.027) as independent predictors for a prolonged BRS resorption, whereas the resorption rate in ACS patients (STEMI, NSTEMI, and unstable angina; n = 13) was significantly higher as compared to patients without ACS (0.62 ± 0.17 vs. 0.43 ± 0.24; p =.012). Conclusion: In humans, BRS resorption rate is significantly influenced by numerous factors. Our data suggest that diabetes and PSLIA are associated with a prolonged resorption process, whereas in ACS patients, BRS resorption appears to be significantly faster.
CRIS-Team Scopus Importer:2019-12-13
Keywords: bioresorbable vascular scaffolds; optical coherence tomography; percutaneous coronary intervention

OCT-assessment of scaffold resorption: analysis of strut intensity via the brs-resorb-index for poly-L-lactic acid bioresorbable vascular scaffolds - Blachutzik, F.; Achenbach, Stephan; Tröbs, Monique; Weissner, M.; Nef, H.; Schlundt, Christian; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Optical coherence tomography: influence of contrast concentration on image quality and diagnostic confidence - Blachutzik, Florian; Achenbach, Stephan; Nef, Holger; Hamm, Christian; Dorr, Oliver; Boeder, Niklas; Tröbs, Monique; Schneider, Reinhard; Röther, Jens; Schlundt, Christian; Marwan, Mohamed (Heart and Vessels, 2017)
OCT requires intracoronary injection of contrast agent to remove blood from the coronary lumen during data acquisition, which is a possible limitation of this method. Aim of this study was to analyze the influence of iodine concentration on image quality and diagnostic certainty of optical coherence tomography (OCT). OCT sequences acquired using contrast agent with a reduced concentration of 150 mg iodine/ml and a standard concentration of 350 mg iodine/ml were analyzed. Cross-sectional images with a spacing of 10 mm were evaluated regarding image quality and diagnostic confidence. A total of 67 OCT sequences acquired in 24 patients were analyzed. 31 sequences were acquired using contrast agent with a concentration of 150 mg iodine/ml and 36 sequences with a concentration of 350 mg iodine/ml. The percentage of remaining blood streaks in the cross sections was significantly lower for 350 mg iodine/ml compared to 150 mg iodine/ml (19 ± 21 vs. 34 ± 26%, p = 0.013). Contrast with 350 mg iodine/ml showed a significantly higher percentage of completely flushed pullback length as compared to 150 mg iodine/ml (78 ± 24 vs. 58 ± 27%, p = 0.004). Diagnostic certainty was significantly higher for 350 mg iodine/ml than for 150 mg iodine/ml (Likert scale average 1.4 ± 0.7 vs. 2.1 ± 1.2, p < 0.001; Likert scale: 1 = absolutely confident, 2 = confident with slight doubts, 3 = doubtful/not confident, 4 = non-diagnostic). Regarding image quality and diagnostic certainty, contrast agent with a concentration of 350 mg iodine/ml is superior to 150 mg iodine/ml.
EVALuna2:33638

Outcome of percutaneous coronary intervention with everolimus-eluting bioresorbable vascular scaffolds in patients with STEMI as compared to stable CAD 2 year results from the German-Austrian ABSORB - Tröbs, Monique; Achenbach, Stephan; Nef, H.; Wiebe, J.; Kastner, J.; Mehili, J.; Muenzel, T.; Naber, C.; Neumann, T.; Richard, G.; Schmermundt, A.; Woehrle, J.; et al. (EUROPEAN HEART JOURNAL, 2018)
CRIS-Team WoS Importer:2019-03-15

Overlapping implantation of bioresorbable novolimus-eluting scaffolds: an observational optical coherence tomography study - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian; et al. (Heart and Vessels, 2017)
Overlapping implantation of bioresorbable vascular scaffolds is frequently necessary, but its influence on vessel and scaffold structure has not been thoroughly analyzed previously. The aim of this study was to analyze the acute effects of overlapping implantation on BRS as determined by optical coherence tomography (OCT). A total of 38 patients with de novo coronary artery stenoses who underwent OCT in the context of implantation of novolimus-eluting BRS (DESolve, Elixir Medical Corporation, Sunnyvale, California, USA) were investigated. In 15 patients, overlapping implantation of two BRS was performed, while 23 patients with implantation of one single BRS served as the control group. OCT data were retrospectively analyzed regarding acute scaffold implantation results. There were no significant differences between the overlap and control group in terms of residual in-scaffold area stenosis, scaffold area, mean or minimal lumen area, eccentricity index, incomplete scaffold apposition area or malapposition. While strut fracture was slightly more frequent in BRS with overlap its incidence was low overall. In patients with overlapping BRS, overlap segments did not display smaller lumen areas than segments without overlap (mean lumen area overlap: 8.16 ± 2.97 mm2vs. no overlap: 7.70 ± 2.55 mm2; p = 0.71; minimal lumen area overlap: 6.83 ± 2.71 mm2vs. no overlap: 6.17 ± 2.58 mm2; p = 0.37). Acute mechanical performance of novolimus-eluting BRS is not impaired by overlapping implantation. It can be assumed that vessel expansion compensates for the double scaffold layer in the overlap area resulting in a similar lumen area in overlap areas and in those with a single strut layer.
EVALuna2:33634

Percutaneous coronary intervention of unprotected left main stenoses - Procedural data and outcome depending on SYNTAX I Score - Blachutzik, Florian; Achenbach, Stephan; Röther, Jens; Tröbs, Monique; Schneider, Reinhard; Schlundt, Christian; Marwan, Mohamed (Cardiovascular Revascularization Medicine, 2018)
BACKGROUND: We hypothesized that SYNTAX I score is a predictor for procedure complexity in left main PCI. Procedure complexity, duration and contrast load may contribute to adverse outcome of complex left main percutaneous coronary intervention (PCI). METHODS: In 105 consecutive patients who underwent PCI of unprotected left main coronary artery stenoses between 2014 and 2016, clinical parameters as well as PCI characteristics and follow-up data were analyzed. RESULTS: The mean SYNTAX I score was 29 ± 12, with 66 patients having a SYNTAX I score ≤ 32 and 39 patients a SYNTAX I score > 32. In patients with high SYNTAX I score vs. low-to-intermediate SYNTAX I score, single stent techniques were performed significantly less frequently (18% vs. 68%; p < 0.001), while Crush (44% vs. 5%; p < 0.001) and Culotte techniques (20% vs. 5%; p = 0.003) were performed significantly more frequently. Procedural success was achieved in all 105 cases without periprocedural mortality. During follow up, repeat PCI was necessary significantly more frequently in patients with high compared to patients with low-to-intermediate SYNTAX I score (34% vs.13%; p = 0.003). Nevertheless, overall mortality did not differ between patients with high vs. low-to-intermediate SYNTAX I score (20% vs. 18%). CONCLUSIONS: PCI strategies for the treatment of left main coronary artery stenoses get significantly more complex with increasing SYNTAX I scores. While this translates into a significantly longer procedure duration and contrast load, short-term outcome seems not to be influenced by the SYNTAX I score.
EVALuna2:213082

Post-dilatation after implantation of bioresorbable everolimus- and novolimus-eluting scaffolds: an observational optical coherence tomography study of acute mechanical effects - Blachutzik, Florian; Boeder, Niklas; Wiebe, Jens; Mattesini, Alessio; Doerr, Oliver; Most, Astrid; Bauer, Timm; Röther, Jens; Tröbs, Monique; Schlundt, Christian; Achenbach, Stephan; Hamm, Christian W.; et al. (Clinical Research in Cardiology, 2017)
OBJECTIVES: The objective was to investigate the acute mechanical effects of post-dilatation on bioresorbable scaffolds (BRS) as determined by optical coherence tomography (OCT). BACKGROUND: Post-dilatation with high-pressure balloons is regarded as a key component of BRS implantation for treatment of coronary artery stenoses. However, the impact of post-dilatation on BRS in vivo has not been thoroughly investigated. METHODS: OCT was performed after the implantation procedure of 51 everolimus-eluting or novolimus-eluting polylactic acid-based BRS with (n = 27) or without non-compliant balloon post-dilatation (n = 24). The number of malapposed struts, strut fractures, edge dissections, residual in-scaffold area stenosis, and incomplete scaffold apposition area was analyzed over the complete length of each BRS with a spacing of 1 mm. RESULTS: OCT revealed a significantly lower incomplete scaffold apposition area if post-dilatation was performed (0.16 ± 0.49 mm2with post-dilatation vs. 2.65 ± 2.78 mm2without post-dilatation, p < 0.001), as well as a significantly lower absolute number of malapposed struts (1 ± 2 with post-dilatation vs. 13 ± 13 without post-dilatation, p < 0.001). No significant differences regarding residual in-scaffold area stenosis, strut fracture, edge dissection, symmetry index, or eccentricity index were observed in patients with vs. without post-dilatation. CONCLUSION: Post-dilatation of BRS with non-compliant balloons significantly reduces the number of malapposed struts and incomplete scaffold apposition area without inducing higher rates of edge dissection or strut fracture.
EVALuna2:33645

Postdilatation after implantation of bioresorbable everolimus- and novolimus-eluting scaffolds: an observational optical coherence tomography study on acute mechanistic effects - Blachutzik, F.; Boeder, N.; Wiebe, J.; Mattesini, A.; Doerr, O.; Most, A.; Bauer, T.; Koepp, T.; Tröbs, Monique; Röther, Jens; Schlundt, Christian; Achenbach, Stephan; et al. (2016)
EVALuna2:33685

Predictors of Technical Failure in Transradial Coronary Angiography and Intervention - Tröbs, Monique; Achenbach, Stephan; Plank, Pia Maria; Röther, Jens; Klinghammer, Lutz; Blachutzik, Florian; Schlundt, Christian; Marwan, Mohamed (American Journal of Cardiology, 2017)
Transradial access for coronary angiography and intervention is preferred over the femoral approach but can be technically challenging. Identification of predictors of transradial access failure is important, especially in the context of acute coronary syndromes. We therefore retrospectively analyzed 13,095 consecutive patients (66 ± 12 years, 64% male) in whom transradial access was attempted for coronary angiography or intervention to identify predictors of transradial access failure. Angiograms and patient files were systematically reviewed to analyze patient characteristics associated with failure. Transradial access failure rate was 6.8% (909 of 13,095). Patients with transradial access failure were more frequently female (9.5% vs 5.5%; p <0.001), significantly older (68 ± 12 vs 66 ± 12 years, p <0.001), and had a smaller body surface area (1.89 ± 0.21 vs 1.94 ± 0.2 m2; p <0.001). Transradial failure was not significantly more frequent in ST-elevation myocardial infarction versus other patients (8.1% vs 6.9%, p = 0.195). After multivariable adjustment, only female sex (odds ratio [OR] 1.44, p <0.001), higher patient age (OR 1.01/year, p = 0.002), and lower height (OR 0.98/cm, p = 0.004) independently predicted transradial access failure. In conclusion, female sex, higher age, and smaller height independently predict transradial access failure in coronary angiography and intervention. Failure rate in ST-elevation myocardial infarction is not significantly increased.
EVALuna2:33605

Radial versus femoral approach for rotational atherectomy - technical aspects and procedural outcomes - Bargon, Sophie; Achenbach, Stephan; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Ammon, Fabian; Ferstl, Paul; Schacher, Nora (EUROPEAN HEART JOURNAL, 2021)
CRIS-Team WoS Importer:2021-12-10

Rotational atherectomy via the transradial access: success rates, procedural parameters and complications - Ferstl, Paul; Drentwett, Anne-Sophie; Bargon, Sophie; Schacher, Nora; Tröbs, Monique; Marwan, Mohamed; Achenbach, Stephan; Gaede, Luise (Heart and Vessels, 2022)
Radial access is recommended for percutaneous coronary intervention (PCI), but rotational atherectomy remains frequently performed via femoral access. Analyzing the procedural parameters, success rate and complications of rotational atherectomy, performed via radial in comparison to femoral access. We retrospectively analyzed 427 consecutive patients undergoing rotational atherectomy. Procedural parameters and outcome were determined in 171 patients, scheduled for radial and compared to 256 patients with femoral access use. In the radial access group (74 ± 9 years, 84% male), the LAD was most frequently treated (49%). Sheath size was 7F in 59% and 6F in 41%, burr size was 1.5 mm in 46% and 1.25 mm in 14% of patients. A temporary pacemaker was inserted in 14%. Procedural success rate stood at 97%. Access site complications occurred in 4% of patients, which was significantly less frequent than in in 256 patients treated via femoral access (13% p = 0.003). Compared to radial access, femoral access was associated with the use of larger sheaths (p < 0.001), more frequent treatment of non-LAD vessels (58.2% vs. 44.4%, p = 0.013) and a higher rate of temporary pacemaker use (27%; p = 0.001). No differences could be seen in procedural success (p = 0.83) and burr size (p = 0.51). Femoral access (OR 3.33; 95% CI 1.40–7.93), and female sex (OR3.40 95% CI 1.69–6.63) were independent predictors for access site complications. For coronary rotational atherectomy, radial access has a high success rate with overall use of smaller sheaths, but of equally sized burrs as well as a significant lower rate of access site-related complications than femoral access.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Percutaneous coronary intervention; Radial access; Rotational atherectomy; Transradial

Side effects and major adverse cardiac events caused by fractional flow reserve measurement: a systematic review and meta-analysis of 12,215 patients - Altstidl, Johannes Michael; Gaede, Luise; Tröbs, Monique; Marwan, Mohamed; Achenbach, Susanne (EUROPEAN HEART JOURNAL, 2022)
CRIS-Team WoS Importer:2023-03-03

Software-based automated CT analysis for planning TAVI-Procedures: Systematic validation against expert and novice human interpretation - Weber, J.; Göller, Markus; Smolka, S.; Bittner, D. O.; Gaede, L.; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed; Arnold, Martin (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Tako-Tsubo Cardiomyopathy: clinical correlations of typical and atypical left ventricular contraction patterns - Gaede, L.; Herchenbach, A.; Tröbs, Monique; Achenbach, Stephan; Marwan, Mohamed (EUROPEAN HEART JOURNAL, 2019)
CRIS-Team WoS Importer:2020-02-04

Treatment and outcome of coronary artery perforations using a dual guiding catheter technique - Röther, Jens; Tröbs, Monique; Ludwig, Josef; Achenbach, Susanne; Schlundt, Christian (International Journal of Cardiology, 2015)
To evaluate the success rate and outcome of coronary artery perforation treatment using a dual guiding catheter technique.Coronary artery perforation is a rare but severe complication during percutaneous coronary intervention (PCI) with high mortality. The use of a second guiding catheter is a helpful technique to minimize hemorrhage through the perforation during interventional repair.We screened all patients between March 2004 and December 2014 who underwent PCI in our department for the occurrence of peri-interventional coronary perforation that was treated using a dual catheter technique. Patient and lesion characteristics as well as outcome were determined.We identified 8 patients who experienced coronary artery perforations (Ellis grade III) during coronary intervention and were treated using a dual guiding catheter approach. The procedure was technically successful (placement of covered stent and sealing of perforation) in 6 patients. Pericardiocentesis was required in 3 patients (38%). Total mortality was 12% (n=1). No coronary or peripheral vascular access complication occurred due to the use of a second guiding catheter.We suggest that the dual guiding catheter technique is a useful and alternative approach to treat severe Ellis grade III coronary artery perforations that occur in the context of percutaneous coronary interventions.
EVALuna2:12076

Ultra-low dose comprehensive cardiac CT imaging in a patient with acute myocarditis - Tröbs, Monique; Brand, Michael; Achenbach, Stephan; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2014)
The ability of contrast-enhanced CT to detect "late enhancement" in a fashion similar to magnetic resonance imaging has been previously reported. We report a case of acute myocarditis with coronary CT angiography as well as "late enhancement" imaging with ultra-low effective radiation dose.
EVALuna2:11957

Use of coronary physiology to guide revascularization in clinical practice: results of the F(FR)2 registry - Altstidl, Johannes Michael; Achenbach, Stephan; Feyrer, Johannes; Nazli, J. Benedikt; Marwan, Mohamed; Gaede, Luise; Möllmann, Helge; Giesler, Tom; Rittger, Harald; Pauschinger, Matthias; Rudolph, Tanja K.; Moshage, Werner; et al. (Clinical Research in Cardiology, 2024)
Background: Despite the recommendation of coronary physiology to guide revascularization in angiographically intermediate stenoses without established correlation to ischemia, its uptake in clinical practice is slow. Aims: This study aimed to analyze the use of coronary physiology in clinical practice. Methods: Based on a multicenter registry (Fractional Flow Reserve Fax Registry, F(FR)2, ClinicalTrials.gov identifier NCT03055910), clinical use, consequences, and complications of coronary physiology were systematically analyzed. Results: F(FR)2 enrolled 2,000 patients with 3,378 intracoronary pressure measurements. Most measurements (96.8%) were performed in angiographically intermediate stenoses. Out of 3,238 lesions in which coronary physiology was used to guide revascularization, revascularization was deferred in 2,643 (78.2%) cases. Fractional flow reserve (FFR) was the most common pressure index used (87.6%), with hyperemia induced by an intracoronary bolus of adenosine in 2,556 lesions (86.4%) and intravenous adenosine used for 384 measurements (13.0%). The route of adenosine administration did not influence FFR results (change-in-estimate -3.1% for regression model predicting FFR from diameter stenosis). Agreement with the subsequent revascularization decision was 93.4% for intravenous and 95.0% for intracoronary adenosine (p = 0.261). Coronary artery occlusion caused by the pressure wire was reported in two cases (0.1%) and dissection in three cases (0.2%), which was fatal once (0.1%). Conclusions: In clinical practice, intracoronary pressure measurements are mostly used to guide revascularization decisions in angiographically intermediate stenoses. Intracoronary and intravenous administration of adenosine seem equally suited. While the rate of serious complications of wire-based intracoronary pressure measurements in clinical practice seems to be low, it is not negligible. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-06-14
Keywords: Complications; Coronary artery disease; Coronary physiology; Fractional flow reserve (FFR); Registry